Critical factors for the adoption of social impact bonds in addressing hiv - Soares Carvalho, Carlos Henrique; Comini, Graziella Maria; Costa Mathias, Ana Luiza Terra (Future Studies Research Journal: Trends and Strategies, 2024)
Objective: To identify the critical positive and negative factors for the adoption of the Social Impact Contract (CIS) model in actions to combat HIV in the State of Amazonas, Brazil. Method: The research is qualitative, exploratory and descriptive. 17 semi-structured interviews were carried out with representatives of actors usually involved in a CIS: government, investors, intermediaries, Civil Society Organizations and control bodies. Main results: The0020critical positive factors for the adoption of CIS are: testing innovative solutions to social problems with lower risk for the government; customization of solutions for specific audiences; and problem solving together with the public sector. Negative factors included lack of knowledge of the model, lack of qualifications of public managers to work with new contracting models, distrust and conflict of interests between actors, and the uncertainty of return on investment. Relevance/originality: In Brazil, there is a lack of sources of financing for public services in the health sector and, despite the history of relations between the public and private sectors in the country, there is no Social Impact Contract (CIS) in execution. Theoretical/methodological contributions: The study describes the perception of interest groups about CIS; demonstrates the critical positive and negative factors for the adoption of this contracting model by the health sector, especially for the treatment of HIV/AIDS.